A nanodrug system overexpressed circRNA_0001805 alleviates nonalcoholic fatty liver disease via miR-106a-5p/miR-320a and ABCA1/CPT1 axis - Jian Li (BMC, 2021)
Abstract Our study aimed to explore the function of circRNA_0001805 in the pathogenesis of NAFLD and the underlying mechanism. A nanodrug system (GA-RM/GZ/PL) was constructed to overexpress circRNA_0001805 specifically in hepatocytes for the treatment of NAFLD. Fat droplet accumulation in cultured cells and mouse hepatic tissues was detected using Oil Red O or H&E staining. The relative expression of circRNAs, genes associated with lipogenesis was quantified by qRT-PCR. Interactions between circRNA_0001805 and miR-106a-5p/miR-320a, between miR-106a-5p/miR-320a and ABCA1/CPT1 were confirmed by dual-luciferase reporter assay. A novel metalorganic framework nanocarrier (GZ) was prepared from glycyrrhizic acid and zinc ions (Zn2+), and this nanocarrier was loaded with the circRNA_0001805 plasmid to construct a nanocore (GZ/PL). Then, this GZ/PL was coated with a galactose-modified RBC membrane (GA-RM) to generate GA-RM/GZ/PL. CircRNA_0001805 expression was downregulated in FFA-challenged primary hepatocytes, HFD-fed mice and NAFLD patients. Overexpressed circRNA_0001805 attenuated NAFLD development by suppressing lipid metabolism disorder and inflammation. CircRNA_0001805 targeted miR-106a-5p/miR-320a, which served as an upstream inhibitor of ABCA1/CPT1 and collaboratively regulated NAFLD progression. GA-RM/GZ/PL targeted hepatocytes, overexpressed circRNA_0001805, released glycyrrhizic acid to reduce the accumulation of lipids in the liver and played a synergistic role against NAFLD-induced lipid metabolism disorder. Graphical Abstract